PENGARUH PEMBERIAN WAFER RANSUM KOMPLIT YANG DITAMBAHKAN AMPAS SAGU (Metroxylon Sp) TERHADAP PENAMPILAN PRODUKSI SAPI BALI - Triani Adelina; Dewi Ananda Mucra; Anwar Efendi Harahap; Muhammad Syarbini (Jambura Journal of Animal Science, 2020)
The purpose of this research is to study the performance of Bali cow production fed with field grass and complete wafer of sago pulp. The method used is a randomized block design (RBD) with 4 treatments 0% sago pulp, 10% sago pulp, 20% sago pulp, 30% sago pulp, and 2 replication. Variable researched are the increased consumption, body weight gain, feed conversion ratio. Data is processed according to diversity analysis of the random group obtained by the mean shows no significant importance (P 0,05) to food consumption, body weight gain, and wafer conversion were relatively similar during the study. Based on the research, it can be concluded that the use of complete wafers with basic ingredients 30% sago pulp cannot improve the production performance in terms of consumption feed, growth in body weight, and feed conversion. Consumption of feed is about 4,66 – 4,83 kg/head/day, body growth between 0,00 – 0,455 kg/head/day and the range of conversion is between 0,00 – 24,83.